Error analysis in complex sentences written by Indonesian students from the English education department - Adaninggar Septi Subekti (Universitas Syiah Kuala, 2018)
This study was aimed to analyse errors made by learners in writing four types of complex sentences; complex sentences with adjective clauses, noun clauses, adverb clauses, and multiple-clause structures in an Essay Writing class. This study was done based on the realisation that learners' grammatical knowledge is not always translated into accurate language production in real writing contexts and as a continuation of a previous study with the same participants which found that learners' mastery of complex sentence structure affected their L2 writing achievements. Through document analysis of 40 essays, by these learners, using Thematic Analysis, the present study found five major themes of errors. They were lack of tense consistency, errors of omission, which included omission of verbs, omission of subjects and verbs, and omission of subjects, errors of addition, incorrect verb formations (double finite verbs), and the combination of several errors. Using Error Analysis as a framework, some possible contributing factors were further examined. Based on the findings, pedagogical implications and limitations, along with suggested directions for future research were also presented.